Hydroquinone exposure alters the morphology of lymphoid organs in vaccinated C57Bl/6 mice. (February 2020) - Fabris, André Luis; Nunes, Andre Vinicius; Schuch, Viviane; de Paula-Silva, Marina; Rocha, GHO; Nakaya, Helder I.; Ho, Paulo Lee; Silveira, Eduardo L.V.; Farsky, Sandra Helena Poliselli
Abstract: The influenza is a common viral infection that can be fatal, especially in high-risk groups such as children, pregnant women, elderly, and immune-deficient individuals. Vaccination is the most efficient approach to prevent the spreading of viral infection and promote individual and public health. In contrast, exposure to environmental pollutants such as cigarette smoke reduces the efficacy of vaccination. We investigated whether chronic exposure to hydroquinone (HQ), the most abundant compound of the tobacco particulate phase, could impair the adaptive immune responses elicited by influenza vaccination. For this, adult male C57BL/6 mice were daily exposed to either nebulized HQ or PBS for 1 h for a total of eight weeks. At weeks 6 and 8, the mice were primed and boosted with the trivalent influenza vaccine via IM respectively. Although the HQ exposure did not alter the body weight of the mice and the biochemical and hematological parameters, the pollutant increased the oxidative stress in splenocytes of immunized animals, modified the morphology of spleen follicles, and augmented the size of their lymph nodes. The lymphoid organs of HQ-exposed mice presented a similar number of vaccine-specific IgG-secreting cells, titers of vaccine-specific total IgG, and respective subclasses. Transcriptome studies with HQ, benzene, or cigarette smoke exposure were also analyzed. The genes up-regulated upon pollutant exposure were associated with neutrophil migration and were shown to be co-expressed with antibody-secreting cell genes. Therefore, these findings suggest that HQ exposure may trigger an immune-compensatory mechanism that enhances the humoral responses induced by influenza vaccination. Graphical abstract: Image 1 Highlights: Repeated in vivo HQ exposure caused oxidative stress in murine splenocytes. HQ exposure disorganized the lymphoid organ structure post influenza vaccination. HQ exposure did not harm the influenza vaccine-derived cellular and humoral responses. Exposure to benzene, cigarette smoke, or HQ changed the expression of immune genes. Neutrophil and B-cell genes were co-expressed upon in vivo HQ and benzene exposure.